INTERNATIONAL LEGAL ISSUES OF THE IMMUNITY OF SITTING HEADS OF STATE AND THE INTERNATIONAL CRIMINAL COURT’ JURISPRUDENCE - Bukuru Jean Baptiste (Электронное приложение к Российскому юридическому журналу, 2019)
The article deals with international legal issues relating to the immunity of the sitting heads of state in the context of the International Criminal Court’s activities. The main attention is paid to the analysis of customary and conventional norms of international law on the immunity of heads of state, the positions of the International Court of Justice, the UN International Law Commission and the practice of the International Criminal Court (ICC) vis-à-vis the heads of states that are not parties to the Rome Statute of the ICC. The author argues that there are contradictions between the provisions of the Rome Statute of the ICC, the customary international-law norms on the immunity of heads of state and the provisions of other international treaties, in particular the Vienna Convention on the Law of Treaties of 1969, and that the heads of states that are not parties to the Rome Statute of the ICC continue to enjoy immunity until their states take other measures to waiver their immunity